A phase Ib study of utomilumab (PF-05082566) in combination with mogamulizumab in patients with advanced solid tumors. Issue 1 (4th December 2019) - Cohen, Ezra E. W.; Pishvaian, Michael J.; Shepard, Dale R.; Wang, Ding; Weiss, Jared; Johnson, Melissa L.; Chung, Christine H.; Chen, Ying; Huang, Bo; Davis, Craig B.; Toffalorio, Francesca; Thall, Aron; et al.
Abstract : Background: Expressed on activated T and natural killer cells, 4-1BB/CD137 is a costimulatory receptor that signals a series of events resulting in cytokine secretion and enhanced effector function. Targeting 4-1BB/CD137 with agonist antibodies has been associated with tumor reduction and antitumor immunity. C-C chemokine receptor 4 (CCR4) is highly expressed in various solid tumor indications and associated with poor prognosis. This phase Ib, open-label study in patients with advanced solid tumors assessed the safety, efficacy, pharmacokinetics, and pharmacodynamics of utomilumab (PF-05082566), a human monoclonal antibody (mAb) agonist of the T-cell costimulatory receptor 4-1BB/CD137, in combination with mogamulizumab, a humanized mAb targeting CCR4 reported to deplete subsets of regulatory T cells (Tregs). Methods: Utomilumab 1.2–5 mg/kg or 100 mg flat dose every 4 weeks plus mogamulizumab 1 mg/kg (weekly in Cycle 1 followed by biweekly in Cycles ≥2) was administered intravenously to 24 adults with solid tumors. Blood was collected pre- and post-dose for assessment of drug pharmacokinetics, immunogenicity, and pharmacodynamic markers. Baseline tumor biopsies from a subset of patients were also analyzed for the presence of programmed cell death-ligand 1 (PD-L1), CD8, FoxP3, and 4-1BB/CD137. Radiologic tumor assessments were conducted at baseline and on treatment every 8 weeks. Results: No dose-limiting toxicities occurred and the maximum tolerated dose was determined to be at least 2.4 mg/kg per the time-to-event continual reassessment method. No serious adverse events related to either treatment were observed; anemia was the only grade 3 non-serious adverse event related to both treatments. Utomilumab systemic exposure appeared to increase with dose. One patient with PD-L1–refractory squamous lung cancer achieved a best overall response of partial response and 9 patients had a best overall response of stable disease. No patients achieved complete response. Objective response rate was 4.2% (95% confidence interval: 0.1–21.1%) per RECIST 1.1. Depletion of Tregs in peripheral blood was accompanied by evidence of T-cell expansion as assessed by T-cell receptor sequence analysis. Conclusions: The combination of utomilumab/mogamulizumab was safe and tolerable, and may be suitable for evaluation in settings where CCR4-expressing Tregs are suppressing anticancer immunity. Trial registration: ClinicalTrials.gov identifier: NCT02444793 .